2017
DOI: 10.21764/efd.01513
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmen Adaylarının Sürdürülebilir Çevreye İlişkin Davranış Düzeylerinin İncelenmesi

Abstract: The purp.ose of this study is to determine candidates of pre-school teachers' behavior levels towards sustainable environment. The cross-sectional survey was employed in the present study, which was conducted within the quantitative paradigm. The population of the study consists of pre-school teachers attending the undergraduate programs of pre-school education at state universities in Turkey, and the sample of the study is composed of 1,049 pre-service teachers studying at the undergraduate programs of pre-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
5
0
4
Order By: Relevance
“…Because there is an environmental education course in the second year, second grade students might have higher attitudes towards sustainable environment than their counterparts (Çimen & Benzer, 2019). However, results of the study conducted by Uludağ, Karademir and Cingi (2017) indicated that preservice early childhood teachers did not differ from each other in terms grade level. The last inquiry of this study elicited a small relationship between pre-service teachers' environmental education self-efficacy beliefs and their attitudes toward sustainable environment.…”
Section: Conclusion and Discussionmentioning
confidence: 81%
“…Because there is an environmental education course in the second year, second grade students might have higher attitudes towards sustainable environment than their counterparts (Çimen & Benzer, 2019). However, results of the study conducted by Uludağ, Karademir and Cingi (2017) indicated that preservice early childhood teachers did not differ from each other in terms grade level. The last inquiry of this study elicited a small relationship between pre-service teachers' environmental education self-efficacy beliefs and their attitudes toward sustainable environment.…”
Section: Conclusion and Discussionmentioning
confidence: 81%
“…Bu çalışmalarda da en fazla nicel araştırma yöntemlerinden biri olan tarama deseni kullanılmıştır. Çalışmaların amaçları incelendiğinde genellikle mevcut durumun ortaya koyulmasının amaçlandığı görülmüştür (Uludağ, Karademir ve Cingi, 2017;Ültay, Ültay ve Çilingir, 2019;Toran, 2016). Var olan durumun ortaya koyulması, ilgili yöntem olarak, tarama yönteminin seçilmesini gerektirmiş olabilir.…”
Section: Geçerlik Ve Güvenirlikunclassified
“…Preschool period is a period in which children's curiosity and desire to learn are intense. In this respect, the preschool period is very important for children to get to know the environment they live in, to develop a positive attitude about their environment, to gain awareness of environmental problems and environmental protection (Uludağ, Karademir, & Cingi, 2017). For this reason, permaculture education to be given to children at an early age; will be able to raise the awareness of children on issues such as their nature and environmental problems and finding solutions to these problems, being sensitive to the environment, and ecological sustainability.…”
Section: Preschool Education and Permaculturementioning
confidence: 99%
“…Okul öncesi dönem, çocuklarda merak duygusu ve öğrenme isteğinin yoğun olduğu bir dönemdir. Bu açıdan okul öncesi dönem, çocukların yaşadıkları çevreyi tanıma, çevrelerine dair olumlu tutum geliştirme, çevre sorunlarına karşı farkındalık ve çevre koruma bilinci kazanmalarında oldukça önemlidir (Uludağ, Karademir ve Cingi, 2017). Bu nedenle çocuklara erken yaşlarda verilecek permakültür eğitimi; onların doğa ve çevre sorunlarına ve bu sorunlara çözüm yolları bulma, çevreye duyarlı olma, ekolojik sürdürülebilirlik gibi konularda çocukları bilinçlendirebilecektir.…”
Section: Introductionunclassified